Modelling cell–matrix interactions in airway smooth muscle cells - Irons, Linda (2019)
Tissues, in both humans and animals, consist of cells embedded in a dynamic scaffold known as the extracellular matrix (ECM). Cells interact with the ECM through the process of cell–matrix adhesion, and these interactions, mediated by transmembrane proteins called integrins, are fundamental in regulating a diverse range of physiological processes. The focus of this thesis is on airway smooth muscle (ASM) cell–matrix adhesion, which regulates the transmission of contractile forces generated within ASM cells to the ECM. This is of particular importance in the context of asthma, where contraction of ASM cells, and the subsequent transmission of contractile forces to the surrounding tissue, leads to a narrowing of the airways called bronchoconstriction. In this thesis, we develop mathematical models of ASM cell–matrix adhesion; our objective is to investigate how integrin-mediated adhesions are affected by the dynamic mechanical environment of the in vivo airway. In particular, we aim to gain insight into how integrins respond to tidal breathing and deep inspirations (DIs), since changes in integrin dynamics may affect the extent of airway narrowing during bronchoconstriction.